Regulation of glioma cell invasion by 3q26 gene products PIK3CA, SOX2 and OPA1 - Schaefer, Thorsten (Brain Pathol, 2018)
Diffuse gliomas progress by invading neighboring brain tissue to promote postoperative relapse. Transcription factor SOX2 is highly expressed in invasive gliomas and maps to chromosome region 3q26 together with the genes for PI3K/AKT signaling activator PIK3CA and effector molecules of mitochondria fusion and cell invasion, MFN1 and OPA1. Gene copy number analysis at 3q26 from 129 glioma patient biopsies revealed mutually exclusive SOX2 amplifications (26%) and OPA1 losses (19%). Both forced SOX2 expression and OPA1 inactivation increased LN319 glioma cell invasion in vitro and promoted cell dispersion in vivo in xenotransplanted D. rerio embryos. While PI3 kinase activity sustained SOX2 expression, pharmacological PI3K/AKT pathway inhibition decreased invasion and resulted in SOX2 nucleus‐to‐cytoplasm translocation in an mTORC1‐independent manner. Chromatin immunoprecipitation and luciferase reporter gene assays together demonstrated that SOX2 trans‐activates PIK3CA and OPA1. Thus, SOX2 activates PI3K/AKT signaling in a positive feedback loop, while OPA1 deletion is interpreted to counteract OPA1 trans‐activation. Remarkably, neuroimaging of human gliomas with high SOX2 or low OPA1 genomic imbalances revealed significantly larger necrotic tumor zone volumes, corresponding to higher invasive capacities of tumors, while autologous necrotic cells are capable of inducing higher invasion in SOX2 overexpressing or OPA1 knocked‐down relative to parental LN319. We thus propose necrosis volume as a surrogate marker for the assessment of glioma invasive potential. Whereas glioma invasion is activated by a PI3K/AKT‐SOX2 loop, it is reduced by a cryptic invasion suppressor SOX2‐OPA1 pathway. Thus, PI3K/AKT‐SOX2 and mitochondria fission represent connected signaling networks regulating glioma invasion.